Znaczenie witaminy D w występowaniu wybranych schorzeń = The importance of vitamin D in the presence of selected diseases - Respondek, Malwina; Pudło, Hanna (Journal of Education, Health and Sport, 2016)
Respondek Malwina, Pudło Hanna. Znaczenie witaminy D w występowaniu wybranych schorzeń = The importance of vitamin D in the presence of selected diseases. Journal of Education, Health and Sport. 2016;6(9):653-663. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.158953 http://ojs.ukw.edu.pl/index.php/johs/article/view/3901 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. Znaczenie witaminy D w występowaniu wybranych schorzeń The importance of vitamin D in the presence of selected diseases Malwina Respondek1, Hanna Pudło1 1Katedra Dietetyki, Wydział Zdrowia Publicznego w Bytomiu, Śląski Uniwersytet Medyczny w Katowicach 1Department of Dietetics, School of Public Health, Medical University of Silesia in Katowice Słowa kluczowe MESH: Vitamin D, metabolism, supplementation Słowa kluczowe: witamina D, metabolizm, suplementacja Streszczenie W ostatnich latach istotnie zmieniło się postrzeganie roli witaminy D w organizmie, której przypisywano głównie udział w regulacji gospodarki wapniowo-fosforanowej oraz zapobieganie krzywicy u dzieci i osteoporozie u dorosłych. Obecnie witaminę D postrzega się bardziej jako hormon steroidowy niż substancję o działaniu witaminowym. Odkrycie receptora VDR (Vitamin D Receptor) w większości komórek pozaszkieletowych oraz kolejne badania epidemiologiczne potwierdzają oddziaływanie witaminy D na funkcjonowanie wielu układów w organizmie tj. utrzymaniu prawidłowego funkcjonowania układu sercowo-naczyniowego, układu immunologicznego, w profilaktyce przeciwnowotworowej i cukrzycy. Summary In recent years significantly changed perception of the role of vitamin D in the body, which was attributed mainly involved in the regulation of calcium –phosphate and the prevention of rickets in children and osteoporosis in adults. Currently, vitamin D is seen more as a steroid hormone than a substance with vitamin . The discovery of VDR (Vitamin D Receptor) receptor in most cells and further epidemiological studies confirmed the impact of vitamin D on the functioning of many body systems it means role of vitamin D in cardiovascular health, immune system, diabetes and cancer prevention.